The Way Back Home - North, Freya (London HarperCollinsPublishers, 2014)
Do you remember the summer you were fifteen? Oriana has returned to the village she grew up in for the first time in years. Staying with her mother and stepfather, she's guarded about what has caused the break up of her relationship and her return home from America. But as she finds herself increasingly drawn to Windward, the huge house that was the chaotic artists' community where she was born, it becomes clear that there is more to be untangled from the past than the present .
Keywords: Life change events -- Friendship in children -- Manners and customs